Photocatalytic alginate fuel cells for energy production and refining of macroalgae. Issue 57 (19th July 2017) - Mazumder, Joyotu; Yoshikawa, Hiroyuki; Miyake, Hideo; Shibata, Toshiyuki; Tamiya, Eiichi
Abstract : An alginate fuel cell comprising a TiO2 -modified carbon sheet (TiO2 /C) anode was developed. The power output of the fuel cell and decomposition of alginate were enhanced by solar irradiation of the anode. Abstract : Using unused biomass, such as inedible brown macroalgae, as an alternative energy and chemical feedstock is important because these materials are cultivated easily and do not compete with food products. In this study, carbon electrodes modified with titanium dioxide (TiO2 ) were fabricated and utilized for the photocatalyzed electrochemical oxidation of alginate, a structural polymer derived from brown macroalgae. A prototype fuel cell comprising a TiO2 -modified carbon sheet (TiO2 /C) electrode immersed in an alkaline solution containing 0.2% (w/v) alginate was irradiated with artificial solar light, yielding a maximum power output of 81 μW cm −2 at an irradiation intensity of 150 mW cm −2 . Furthermore, optical absorption and high-performance liquid chromatography analyses of the alginate solution after continuous fuel cell operation for 24 h showed that (1) artificial solar irradiation of the TiO2 /C anodes enhances the oxidation of alginate to generate species with CO groups and (2) the generated species include those of lower molecular weights compared to those of the alginate polymer, possibly comparable to that of the constituent monomer unit of alginate. These results suggest that the oxidation pathway includes glycosidic bond cleavage of the alginate polymer chain in a manner similar to alginate oxidation using much harsher oxidizing agents.